2018
DOI: 10.1155/2018/3178472
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Related Therapies for Treatment of Postoperative Ileus in Colorectal Cancer: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Delays in recovery of intestinal function following abdominal surgery are associated with longer hospital stays, increased postoperative complications, and higher costs to the health care system. Studies of acupuncture for postoperative ileus and other postoperative issues have reported improvements. This systematic review and meta-analysis aimed to assess whether acupuncture assisted recovery following surgery for colorectal cancer (CRC). Randomized controlled trials (RCTs) were identified from major English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 37 publications
0
46
0
1
Order By: Relevance
“…The first reason for this decision is that the outcomes of gastric motility recovery are relatively objective, and the placebo effect has little effect on results. In addition, a systematic review suggested that acupuncture has a better effect than sham acupuncture for promoting the recovery of gastrointestinal function [31] . The purpose of this study is to verify whether routine treatment combined with EA is superior to routine treatment alone for gastrointestinal motility recovery after colorectal cancer surgery; thus, we chose routine treatment as the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The first reason for this decision is that the outcomes of gastric motility recovery are relatively objective, and the placebo effect has little effect on results. In addition, a systematic review suggested that acupuncture has a better effect than sham acupuncture for promoting the recovery of gastrointestinal function [31] . The purpose of this study is to verify whether routine treatment combined with EA is superior to routine treatment alone for gastrointestinal motility recovery after colorectal cancer surgery; thus, we chose routine treatment as the control group.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Secondary Outcomes . (1) The recovery of gastrointestinal function (first defecation time, first flatus time, and first bowel sounds time) [ 28 ]. (2) Adverse effects (relevant symptoms caused by acupuncture).…”
Section: Methodsmentioning
confidence: 99%
“…Laser acupuncture (LA) combines the characteristics of traditional metal-needle acupuncture and low-level laser therapy. While acupuncture has been reported to promote the recovery time of postoperative ileus in patients with colorectal cancer, [ 5 ] the application of LA for ASBO is very rare, and only 1 pre-clinical study has shown low level laser therapy to be effective in preventing intra-abdominal adhesions in rabbits without compromising the strength and healing of the abdominal wall. [ 6 ] We assume that conventional treatment combined with LA will be effective for reducing the need for surgery through eliminating the symptoms of ASBO.…”
Section: Introductionmentioning
confidence: 99%